Different estrous induction protocols during the non- breeding season in Assaf ewes - Baher Abu Gazal; Hatem Atalla (My University, 2012)
This experiment was designed to measure the effect of pregnant mare serum gonadotrophin (PMSG) levels (300 or 600 I.U.) and the progestagen impregnated intravaginal sponge application method (one sponge for 14 d or two sponge each for 7 d) on estrus response, onset and duration of estrus, litter size and serum progestagen concentrations during estrus period and early pregnancy in 20 Assaf ewes. In April, which considered a non-breading season for ewes in Palestine, intravaginal sponges containing 60 mg Medroxyprogesterone acetate (MAP) were inserted, after seven days of sponge insertion, sponges were removed and new sponges were inserted to 10 ewes of the 20 ewes used in the trial. Following progesterone withdrawal at the 14th day, 5 ewes from each group received an intramuscular injection of either 300 or 600 I.U. PMSG. Although, some slight differences were obtained but there was no significant differences between the
two different progesterone application methods nor the two different PMSG doses. So one sponge followed by 300 I.U. PMSG can be used to synchronize estrus successfully and with lower cost than using two sponges or high PMSG doses.

This experiment was designed to measure the effect of pregnant mare serum gonadotrophin (PMSG) levels (300 or 600 I.U.) and the progestagen impregnated intravaginal sponge application method (one sponge for 14 d or two sponge each for 7 d) on estrus response, onset and duration of estrus, litter size and serum progestagen concentrations during estrus period and early pregnancy in 20 Assaf ewes. In April, which considered a non-breading season for ewes in Palestine, intravaginal sponges containing 60 mg Medroxyprogesterone acetate (MAP) were inserted, after seven days of sponge insertion, sponges were removed and new sponges were inserted to 10 ewes of the 20 ewes used in the trial. Following progesterone withdrawal at the 14th day, 5 ewes from each group received an intramuscular injection of either 300 or 600 I.U. PMSG. Although, some slight differences were obtained but there was no significant differences between the
two different progesterone application methods nor the two different PMSG doses. So one sponge followed by 300 I.U. PMSG can be used to synchronize estrus successfully and with lower cost than using two sponges or high PMSG doses.
Different estrous induction protocols during the non- breeding season in Assaf ewes